River Buffalo Meat Production and Quality: Sustainability, Productivity, Nutritional and Sensory Properties - Guerrero-Legarreta, Isabel; Napolitano, Fabio; Cruz-Monterrosa, Rosy; Mota-Rojas, Daniel; Mora-Medina, Patricia; Ramírez-Bribiesca, Efren; Bertoni, Aldo; Berdugo-Gutiérrez, Jesus; Braghieri, Ada (Journal of Buffalo Science, 2020)
One of the most important challenges facing today’s society is feeding a growing world population. This review aims to examine the available information to assess the potential of river buffalo as a meat producer with a focus on the sustainability of the supply chain and on meat quality in terms of nutritional and sensory properties. Traditionally, buffalo meat came from old, culled animals in rural agricultural regions where animals were slaughtered at the end of their productive life as dairy or draught animals. Therefore, the meat had low quality. However, when younger animals are used, buffalo meat is generally well appreciated by consumers. Buffaloes can adapt to different production systems and convert poor-quality high fiber feedstuffs into high-quality products, including meat, with a lower degree of competition with human nutrition. In addition, although requiring more land, extensive production systems may have lower environmental impacts due to the low inputs used in the productive process and show higher levels of animal welfare. Although weight gains and dressing percentages are generally lower than in cattle, the meat is characterized by better nutritional properties (low fat and cholesterol contents, high-quality protein, and unsaturated fatty acids). In addition, the use of appropriate production systems might improve its sensory properties. Therefore, buffalo meat may be considered a good option to meet the increasing demand for food for human consumption.